(untitled) (Journal of Environmental Microbiology and Toxicology, 2021)
Butachlor is a chloroacetanilide herbicide that is selective in action and commonly used for pre-emergence control of weeds. It is believed to have range of toxicity from acute to chronic and also can cause DNA strand breaks and chromosomal aberrations in humans. This study was aimed at characterizing the potential of previously isolated bacteria for butachlor degradation. The isolates from culture collection, labelled A-F were screened for butachlor degradation on Bushnell Hass agar media with butachlor as a sole carbon source. Isolate A (molybdenum-reducing and aniline-degrading Pseudomonas sp.) was observed to grow best and tolerated the highest concentration of butachlor supplemented in the media after 72 h of incubation at 37 ℃. Characterization study revealed that the Pseudomonas sp. can utilize and grow with butachlor at optimum pH between 6.0 - 6.5, temperature between 30 – 37 ℃ and can tolerate up to 600 mg/L butachlor concentration with increase in growth as inoculum size increases. Additionally, this bacterial strain shows no lag phase regardless of the concentration of the herbicide used and reach its maximum growth after 24 h of incubation. The ability of this isolate to tolerate and utilize butachlor as sole carbon source makes it suitable for future bioremediation of this toxicant.